Financially stupid people are everywhere : don?t be one of them - Kelly, Jason , 1973- (Wiley, 2010)
"A hard-hitting look at achieving financial freedom by avoiding excessive borrowing and spending. If you don?t actively resist America?s culture of debt, you?ll end up precisely where the government, banks, and big business want you to be: indentured servitude. The mistakes people make with their money are basic, and avoidable, and unless you understand what they are, you?re probably going to repeat them. What you need is someone who can shed light on the obstacles we face and show you how to avoid getting tripped up by them. Financially Stupid People Are Everywhere shows how society is rigged to take as much of your wealth as possible, and simple ways you can resist. It investigates, explains, and offers advice for all those who have fallen into debt, taken a second mortgage, been trapped by credit cards, or found themselves unable to get ahead. Discusses what you can do to stop the destructive cycle of borrowing and spendingIllustrates the four major tenets of getting money right. Highlights how to avoid the many ways that government, banks, and big business try to trap you with debt. To secure your financial future, you must break the dangerous cycle of borrowing and spending, and learn how to guard your wealth against corporate ploys. Financially Stupid People Are Everywhere leads you down the only proven path to financial freedom"